Reformation of Europe or the Church? - Robert Bogešić (Kairos (English Ed.), 2011)
With the end of World War II, the project of unifying Europe started with the goal of avoiding new war conflicts in Europe. The process of building the European system included individual and collective models which were based on cooperation. In relation to other civilizations, the West represents supremacy, but also a civilization that is setting. Euro-Atlantic integrations are faced with the challenges of building collective and all-encompassing systems that can enable stability in political, economic, ecological, religious and other areas of social life. The Christian church has, during its development, experienced various forms of spiritual revival. After the first decade of the 21st century, the churches of Europe are now faced with the great and responsible tasks of achieving spiritual revival as well as spiritual unity, even though their confessional differences represent a great obstacle to the practical application of it. One wonders whether this is a Christianization of secular Europe or a secularization of the Christian church. Does the church need a new Reformation, or was the Counter Reformation sufficient, and the church should be satisfied with its current state?